To solve this system of equations, we can use the method of substitution or elimination.
Let's use the method of substitution:
From the first equation, we can solve for x in terms of y:
-5x + 7y = 67
-5x = -7y + 67
x = (7y - 67)/5
Now, we substitute this expression for x into the second equation:
11x + 12y = 17
11((7y - 67)/5) + 12y = 17
(77y - 737)/5 + 12y = 17
77y - 737 + 60y = 85
137y - 737 = 85
137y = 822
y = 822/137
y = 6
Substituting y = 6 into the expression for x:
x = (7(6) - 67)/5
x = (42 - 67)/5
x = -25/5
x = -5
Therefore, the solution for the system of equations is x = -5 and y = 6.
-5x + 7y = 67
11x + 12y = 17
What is the solution for the system of equations above?
1 answer